Nyctanthes is a member of the Oleaceae - Kiew, Ruth; Baas, Pieter (Indian Academy of Sciences, 1984)
The attributes of Nyctanthes (habit, floral morphology, fruit and seed, stem and leaf anatomy, flower vasculature, embryology, pollen, chromosome number and phytochemistry) are reviewed and found compatible with accommodation of the genus in the Oleaceae, tribe Jasmineae. The treatment of Nyctanthes in Verbenaceae or as a separate does not reflect its true affinities.